2019
DOI: 10.1016/j.clnu.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in selenoprotein genes modulate biomarkers of selenium status in response to Brazil nut supplementation (the SU.BRA.NUT study)

Abstract: Genetic variations in GPX1 and SELENOP genes are associated with different responses of molecular and biochemical biomarkers of Se status after Brazil nut supplementation in healthy Brazilians. The SU.BRA.NUT study was registred at www.clinicaltrials.gov as NCT 03111355.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
1
36
0
1
Order By: Relevance
“…However, different from the variable associations of selenium with components of MetS, no significant association between rs7579 and a component of MetS was observed in our study. As both plasma levels of selenium and the rs7579 polymorphism take part in regulating the gene expression of SELENOP [15], selenium might be involved in the development of MetS partly through SELE-NOP, while the relation between selenium and components of MetS might be attributed to the effect of selenium independent of SELENOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different from the variable associations of selenium with components of MetS, no significant association between rs7579 and a component of MetS was observed in our study. As both plasma levels of selenium and the rs7579 polymorphism take part in regulating the gene expression of SELENOP [15], selenium might be involved in the development of MetS partly through SELE-NOP, while the relation between selenium and components of MetS might be attributed to the effect of selenium independent of SELENOP.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the downregulation of SELENOP expression improved systemic insulin sensitivity and glucose tolerance [14]. A previous study identified a single nucleotide polymorphism (SNP) located in the 3 ′ -untranslated region of the SELENOP gene, namely rs7579, which influenced both SELENOP mRNA expression and protein level [15]. Further studies provided evidence to correlate this SNP with metabolic factors; the SNP was associated with serum lipids and insulin sensitivity index [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Three years later, this same research group showed that supplementation with Brazil nuts (the main source of Se in the world) for 8 weeks in carriers of the C/C genotype (rs1050450) increased mRNA expression of the GPX1 gene ( p = 0.026), whereas that of the T allele did not change. Likewise, SELENOP mRNA expression was higher in carriers of the rare A allele for rs7579 before or after supplementation ( p =< 0.05) [ 74 ]. In addition, there are other studies that have reported similar results in relation to the concentration and activity of the GPx isoforms and SeP influenced by Se supplementation [ 75 , 76 ].…”
Section: Nutritional Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…As anticipated given the function of SELENOP in selenium transport, there were associations between the SELENOP variants and the levels of several selenoproteins that require selenium for synthesis [50,51]. Among these were selenoproteins associated with protection from oxidative stress, a result supported by a cross-sectional study of oxidative stress markers among New Zealand men [52] and a study of individuals supplemented with selenium-rich Brazil nuts [53]. In addition to affecting the levels of SELENOP, these polymorphisms impacted the distribution between two SELENOP isoforms which differ by approximately 10 kDa [54].…”
Section: Selenium Transport Via Selenoprotein P (Selenop) and Selenopmentioning
confidence: 70%